2014
DOI: 10.3390/su6106781
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism Environmental Protection Measures and Their Effects on Protected Areas in China

Abstract: Ecological and environmental protection is the core content of ecotourism development. A quantitative evaluation of the effects of ecotourism environmental protection (hereinafter referred to as EEP) measures on protected areas is conducive to a deeper understanding of the key issues related to ecotourism development in China, thus providing the theoretical basis for formulating the relevant national policies of sustainable ecotourism development in China. This paper first discusses the evaluation index system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…The fact that most ecotourism sites are found in the richer provinces makes sense to a certain extent. Higher GDP allows for increased investment and development potential, so that these provinces can develop ecotourism in their natural areas while lower GDP provinces are still struggling to expand facilities due to limited funding [54]. In general, the high number of scenic sites touting labels of "ecotourism" demonstrate that the concept of ecotourism has been widely adopted in China, reflecting the positive perception of the concept by the Chinese population, which has treated it as a huge marketing opportunity.…”
Section: Ecotourism In China: Misuse or Genuine Development?mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that most ecotourism sites are found in the richer provinces makes sense to a certain extent. Higher GDP allows for increased investment and development potential, so that these provinces can develop ecotourism in their natural areas while lower GDP provinces are still struggling to expand facilities due to limited funding [54]. In general, the high number of scenic sites touting labels of "ecotourism" demonstrate that the concept of ecotourism has been widely adopted in China, reflecting the positive perception of the concept by the Chinese population, which has treated it as a huge marketing opportunity.…”
Section: Ecotourism In China: Misuse or Genuine Development?mentioning
confidence: 99%
“…Unfortunately, as previously mentioned for other regions of the world, the apparent success of ecotourism development has not come without cost. Although extensive survey results over the majority of provinces in mainland China have reported a positive ecotourism development performance in forest parks [51] with some differences among provinces [54], several studies have found increasing pressure on natural resources and damage to ecosystems due to an excessively large numbers of visitors [55], poor behavior of tourists [56] and inadequate management at several administrative levels [46,54,57,58]. Moreover, other fundamental aims of the ecotourism model such as the fair distribution of income among stakeholders and the environmental awareness of tourists, were rarely achieved [36,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The industry accounts for more than 10% of global employment and more than 11% of global GDP (The Mountain Institute, 2000). Furthermore, development policy makers view tourism as a mechanism for achieving socio-economic progress thus total trips of tourist will further increase (Madzara, 2011;Barry, 2012;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The attention is now more focused on the protected areas particularly due to the changing approach to the mass tourism and tendency to move away from the usual tourism attractions (Marzouki et al, 2012). Such an increased interest has led to the emergence of the concept of ecotourism since ecotourism adopts the principles of protecting the natural areas, providing economic contributions to local people and living in an environmentally-conscious manner (Bushell and Eagles, 2007;Korkmaz and Başkalkan, 2011;Akyol and Tolunay, 2012;Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%